Holding Peaceful Assemblies in the Republic of Kazakhstan: Rights of Citizens and Administrative Liability - AVENOV, Timur K. (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018, 2018)
The article considers the matters of constitutional and administrative-legal regulation of the right to peaceful assembly in the Republic of Kazakhstan (RoK) and a number of foreign countries. Since there is a lot of publications dedicated to the study of compliance of this legislation to international standards, the analysis has been conducted by the following criteria: the general characteristic of the right to freedom of assembly from the viewpoint of international and constitutional law standards, the principles of organization and holding of public assemblies, the procedure of organization of a public assembly and its holding, and the liability for breaching this procedure. The author shows that the current incoherence of legal norms in this area prevents from developing a unified legal model for administrative liability for breaching public order and safety when holding mass events. Based on the study of normative and research materials in administrative and constitutional law, legal principles and approaches to freedom of assembly in international law and the law of a number of foreign countries, the author proposes options to improve the conceptual framework of legislation concerning assembly and mass events, to formulate proposals that will allow efficiently and legally applying administrative liability for breaching the RoK law concerning the procedure of organization and holding of peaceful assemblies, rallies, marches, pickets and demonstrations. Primary provisions and conclusions of the article can be used in scientific and practical activity when considering issues of holding liable for offences infringing constitutional rights of citizens and the established procedure for organizing and holding peaceful assemblies, rallies, marches, pickets and demonstrations, and to reform the norms of legislation on administrative offences.